Should trees have standing? and other essays on law, morals and the environment - Stone, Christopher D. (Oceana Pub. Dobbs FerryUS, 1996)
Looks at legal rights for the environment. Reflects on sustainable development, the Convention on Biologivcal Diversity and an environmental ethic for the 21st century.